THE IMPLEMENTATION OF CONSTITUTIONAL COURT DECISION NUMBER 13/PUU-XV/2017 ON INTER-EMPLOYEE MARRIAGE POLICIES AT LION PARCEL MEDAN - Sutri Widiyaningsih Br Ginting; Khalid Khalid (Journal Analytica Islamica, 2026)
The right to form a family through marriage is a human right that is constitutionally guaranteed in Article 28B paragraph (1) of the 1945 Constitution of the Republic of Indonesia. However, in private sector employment practices, this right is still often restricted through internal company policies that prohibit marriage between employees. This study aims to analyze the implementation of Constitutional Court Decision Number 13/PUU-XV/2017 in employment practices at Lion Parcel Medan and identify obstacles that hinder its implementation. This study uses an empirical juridical approach with data collection methods through literature studies and in-depth interviews with employees and company management. The results of the study indicate that although the Constitutional Court Decision is final and binding and expressly prohibits termination of employment due to marriage between employees, its implementation at Lion Parcel Medan has not been optimal. The main obstacles include the company's internal policies not being revised, the low understanding of the law among management and workers, and weak supervision from employment agencies. This study emphasizes the importance of harmonization between constitutional norms and company policies to ensure the protection of workers' rights without neglecting professionalism and organizational governance.